THE INFLUENCE OF SCHOOL PRINCIPALS' LEADERSHIP AND WORK CLIMATE ON THE WORK MOTIVATION OF VOCATIONAL SECONDARY SCHOOL TEACHERS IN DKI JAKARTA - ALIYAH, Siti (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
The aim of this research is to analyze, test and obtain a clear picture of the influence of school principal leadership and work climate on the work motivation of vocational high school teachers in DKI Jakarta. This research uses a quantitative approach and hypothesis testing uses the path analysis method, while the data collection technique uses questionnaires, with a sample of 150 teachers from a population of 240 PNS and P3K teachers in DKI Jakarta, in this case I took the population of PNS and P3K teachers in North Jakarta and the Thousand Islands. Based on the results of hypothesis testing from the research discussion, several conclusions can be put forward as follows: (1) There is a direct positive and significant influence of school principal leadership on the work motivation of vocational school teachers in DKI Jakarta. (2) There is a direct positive and significant influence of work climate on teacher work motivation of vocational school teachers in DKI Jakarta. (3) There is a direct positive and significant influence of the principal's leadership on the work climate at vocational schools in DKI Jakarta.